Correlation of Interest, Knowledge, and Local Wisdom in Implementation Sustainable Development Goals - Martadani, As Noor; Alkatiri, Farid Abud; Huath, Elvi Ratna Irawati (POPULIKA, 2024)
The SDGs (Sustainable Development Goals) program continues the MDGs (Millennium Development Goals) which ended in 2015. Both agendas take the form of sustainable development programs designed by the UNDP (the United Nations Development Program) from the perspective of developed countries. In Indonesia, the sustainable development agenda, especially the SDGs, has been implemented to date but has experienced various obstacles related to issues of public interest and knowledge of the SDGs, as well as the lack of local wisdom values ​​in SDGs programs. Therefore, this research examines the correlation of the extent to which people are interested in acquiring knowledge of sustainable development according to the SDGs framework, including aspects of local wisdom in the SDGs agenda. Data was obtained through a survey of 100 respondents in Yogyakarta City, Yogyakarta Special Region, and then analyzed to see the correlation between interest, knowledge, and local wisdom within the SDGs' sustainable development framework. The research results show that the knowledge related to sustainable development has a positive and significant relationship with interest in the SDGs, including the high level of public understanding of the SDGs program. Apart from that, the level of knowledge of local wisdom is positively and significantly correlated with interest in the SDGs. This can be seen from the fact that people with a high understanding of local wisdom are highly interested in SDGs programs. Keywords:  Interest; Knowledge; Local Wisdom; Sustainable Development.